Pedagogical Potential of Online Museum Learning Resources - Milutinović, Jovana; Selaković, Kristinka (Revija za elementarno izobraževanje, 2022)
The COVID-19 era has changed the way most institutions operate, including museums and their educational activities. The aim of this paper is to investigate the types of online learning resources represented on museum websites, as well as to analyse their pedagogical features. Mixed research was applied, while the sample consists of museums included in the relevant portals that provide visibility for cultural institutions in Serbia. The analysis of the research results made it possible to determine the current level of development of pedagogical features of online museum learning resources and to identify opportunities for their improvement.
Keywords: constructivism, digital resources, education, museum, online learning